The Comorbidity Profile of Neurological Disease in Elderly in the Taman Sari Public Health Center from January to December 2023 - Yulianti, Ika; Banu, Syairah (Acta Neurologica Indonesia, 2024)
Background: The burden of neurological diseases in elderly patients is often underestimated. Therefore, our study aimed to investigate the comorbidity profile of NDs in patients aged 60 years or older at the Taman Sari Public Health Center. Method: This was a retrospective, descriptive study with a cross-sectional design. The data were collected from medical records (e-puskesmas) and SIPTM (Non-Communicable Diseases Surveillance Information System) at the Taman Sari Public Health Center from January to December 2023. The study focuses on patients diagnosed with chronic diseases who also have comorbidities of NDs. Result: Analysis was conducted on 803 individuals, including 382 males and 421 females which revealed that 68.4% of the participants had polyneuropathy, 26.8% were diagnosed with cerebrovascular disease, 2.1% had CNS infection, 1.1% had CNS metabolic disorders, 1.6% of patients exhibited symptoms of dementia. Discussion: The study has shown that polyneuropathy is a prevalent issue, with cerebrovascular diseases exhibiting intermediate to high levels of patient comorbidity. CNS infection with tuberculosis meningitis is the leading cause of CNS infection. Furthermore, metabolic diseases can cause CNS metabolic disorders, while dementia is often associated with patient comorbidity, which significantly influences its clinical progression. Conclusion: Understanding the comorbidity profile of neurological diseases in elderly patients at the Taman Sari District Health Center could improve patient care management and lead to better outcomes.